2021
DOI: 10.1037/cap0000219
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for the extension of rights to medical assistance in dying (MAiD) to mature minors in Canada.

Abstract: Individuals suffering intolerably from a medical condition are legally able to request medical assistance in dying (MAiD) under certain circumstances. MAiD can either entail a physician or nurse practitioner prescribing fatal drugs for the patient to self-administer (physician-assisted suicide) or a physician directly administering lethal drugs (euthanasia). Whereas laws regulating MAiD have been in effect in different areas of the world since 1942, Canada only recently decriminalized MAiD in 2016. Individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…6 In addition, very few clinical studies have explored how the quality of end-of-life care, and other health issues tied to the end-of-life care, is experienced by children. 6 Patton and Dobson completed a review of recent evidence related to MAiD for mature minors in 2021, 7 which confirmed that there remains a lack of primary data collection on this topic.…”
Section: Current State Of the Evidence On Maid For Mature Minorsmentioning
confidence: 92%
See 2 more Smart Citations
“…6 In addition, very few clinical studies have explored how the quality of end-of-life care, and other health issues tied to the end-of-life care, is experienced by children. 6 Patton and Dobson completed a review of recent evidence related to MAiD for mature minors in 2021, 7 which confirmed that there remains a lack of primary data collection on this topic.…”
Section: Current State Of the Evidence On Maid For Mature Minorsmentioning
confidence: 92%
“…7 This position has been criticized by Patton and Dobson, who argue that utilizing age as a criterion for competency undermines both the need to respect dignity of mature minors as well as the significance of responsible caring outlined in the Canadian Code of Ethics for Psychologists. 7 They further argue that there is a need to balance the ethical concerns related to the vulnerability of children and their ability to determine what is in their best interests with allowing people to die with dignity and make choices. 7 Similarly, legal arguments have been made that the exclusion of mature minors from the MAiD legislation is an "act of age discrimination," whereby it exposes mature minors to unjustifiable suffering and inaccurately positions them as incapable.…”
Section: Evidence From Canadamentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Columbia, the legal age for PAD is 7, and in Belgium, there is no specified age limit (Jones & Simpson, 2018). As will be discussed in detail later, the practices and debates in these jurisdictions have ramifications for MAID practices in Canada, as Canada is currently looking into extending MAID criteria to include the above-mentioned populations (e.g., Patton & Dobson, 2020).…”
Section: Assisted Death Today: Canada and Abroadmentioning
confidence: 99%
“…As stipulated in the text of Canada's MAiD legislation, eligibility criteria for termination of life with medical assistance include intolerable suffering, an irremediable medical condition, foreseeable death, mental competence, and age of at least 18 years (Nicol & Tiedemann, 2018;CNA, 2022). Of these, foreseeable death, age restrictions, and mental competence continue to be raised as areas of concern (Buote et al, 2022;Charland et al, 2016;Patton & Dobson, 2020;Variath et al, 2022).…”
Section: The Scope and Significance Of Choicementioning
confidence: 99%